2009
DOI: 10.1534/genetics.108.100271
|View full text |Cite
|
Sign up to set email alerts
|

Multiple SET Methyltransferases Are Required to Maintain Normal Heterochromatin Domains in the Genome of Drosophila melanogaster

Abstract: Methylation of histone H3 lysine 9 (H3K9) is a key feature of silent chromatin and plays an important role in stabilizing the interaction of heterochromatin protein 1 (HP1) with chromatin. Genomes of metazoans such as the fruit fly Drosophila melanogaster generally encode three types of H3K9-specific SET domain methyltransferases that contribute to chromatin homeostasis during the life cycle of the organism. SU(VAR)3-9, dG9a, and dSETDB1 all function in the generation of wild-type H3K9 methylation levels in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 43 publications
4
92
0
Order By: Relevance
“…Drosophila rDNA genes also show moderate levels of H3K9me (Blattes et al 2006;Peng and Karpen 2007), arguing that heterochromatin-mediated repression is a general feature of rDNA regulation. While the Su(var)3-9 enzyme is one of the major H3K9 methyltransferases for Drosophila heterochromatin (Brower-Toland et al 2009), it is unknown how much histone methylation at the rDNA genes is due to the Su(var)3-9 enzyme. In any case, our genetic analysis shows that this enzyme only partially contributes to silencing of the X chromosome rDNA array, suggesting that rDNA silencing may be molecularly distinct from other forms of heterochromatic gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila rDNA genes also show moderate levels of H3K9me (Blattes et al 2006;Peng and Karpen 2007), arguing that heterochromatin-mediated repression is a general feature of rDNA regulation. While the Su(var)3-9 enzyme is one of the major H3K9 methyltransferases for Drosophila heterochromatin (Brower-Toland et al 2009), it is unknown how much histone methylation at the rDNA genes is due to the Su(var)3-9 enzyme. In any case, our genetic analysis shows that this enzyme only partially contributes to silencing of the X chromosome rDNA array, suggesting that rDNA silencing may be molecularly distinct from other forms of heterochromatic gene silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Hairpin line construction was carried out as described (42) except that the piwi fragment was amplified from a cDNA clone, GM05853 (43), using the following primer pair: forward 5′-GCT CTA GAT CCG GTT GAG CTG GTA TCC AAG AA-3′ and reverse 5′-GCT CTA GAA GAT CGT CTC GGT GCG CAT AAC TT-3′. Seven transgenic lines with different insertion sites were recovered (SI Appendix, Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has demonstrated that Su(var)3-9 mutants display defects in H3K9 methylation patterns and reduced pericentric HP1a localization in both the ovary (Schotta et al 2002;Yoon et al 2008) and salivary glands (Brower-Toland et al 2009), and similar phenotypes have been observed in Eggless RNAi KD salivary glands (Brower-Toland et al 2009). When we use the mata driver to knock down either Su(var)3-9 or Eggless protein during meiotic prophase, we observe PHeMAAH defects at levels similar to those observed in HP1a and Piwi knockdown ovaries.…”
Section: Discussionmentioning
confidence: 53%
“…Unfortunately, all publically available Su(var)3-9 hairpins target sequences in this common exon, raising the possibility that the PHeMAAH defects that we observe in Su(var)3-9 KD oocytes result from disruption of eIF-g function rather than reduced H3K9 methyltransferase activity. To further investigate the requirement of the H3K9me2/3 mark for promoting centromere proximal association of achiasmate homologs, we knocked down Eggless (also known as dSETDB1), a second methyltransferase that is also required to maintain the H3K9me2/3 mark in the pericentric heterochromatin (Brower-Toland et al 2009). With two different hairpins targeting different sequences within the Eggless mRNA ( Figure S2), FM7a/X KD oocytes exhibited a significant increase in PHeMAAH defects compared to control oocytes (V20-1: 22.0% in KD vs. 13.6% in control, P = 0.005; V20-2: 28.4% in KD vs. 14.4% in control, P , 0.001; Figure 1F).…”
Section: Knockdown Of Two Different H3k9 Methyltransferases Disrupts mentioning
confidence: 99%